2001
DOI: 10.1093/emboj/20.22.6443
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nuclear poly(A) addition controls the expression of immunoglobulin M secretory mRNA

Abstract: B-cell differentiation is accompanied by a dramatic increase in cytoplasmic accumulation and stability of the IgM heavy chain (mu) secretory mRNA. Despite considerable effort, the mechanism is unknown. We have identified three short motifs upstream of the secretory poly(A) site, which, when mutated in the mu heavy chain gene, significantly increase the accumulation of the secretory form of poly(A)(+) mRNA relative to the membrane form and regulate the expression of the secretory poly(A) site in a developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 52 publications
4
70
0
Order By: Relevance
“…The full-length cDNAs of HMGA1a, HMGA1b, and U1-70K were amplified by RT-PCR with attached BamHI and EcoRI sites, and subcloned into pcDNA3(+) vector (Invitrogen) between corresponding restriction enzyme sites. U1-A expression plasmid 37 was a generous gift from Dr S Gunderson.…”
Section: Methodsmentioning
confidence: 99%
“…The full-length cDNAs of HMGA1a, HMGA1b, and U1-70K were amplified by RT-PCR with attached BamHI and EcoRI sites, and subcloned into pcDNA3(+) vector (Invitrogen) between corresponding restriction enzyme sites. U1-A expression plasmid 37 was a generous gift from Dr S Gunderson.…”
Section: Methodsmentioning
confidence: 99%
“…The forward primers were as follows: for V1S1 and 2, CCGGAATTCCGGACCGTGGACAAGTggtgaGGTAAACCCtgtgTGTACAATGTCTCC-CTGATCATGTCTG; for V1S1, CCGGAATTCCGGACCGTGGACAAGTggtgacGGTAAACCCACACTGT ACAATGTCTCC; and for V1S2, CCGGAATTCCGGACCGTGGACAAGTCCACTGGGTAAACCCtgtgTGTAC-AATGTCTCCCTGATCATGTCTG. The reverse primer was: GCGTC-TAGATAGGG TGGAGGCAAGTATGC as previously described (13).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that the change in stability is regulated by the addition of a poly(A) tail to the secretory mRNA (13). The U1A protein binds upstream of the secretory poly(A) site and inhibits polyadenylation of the secretory mRNA in a developmentally regulated manner.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The level of a specific mRNA transcript within a cell is regulated by either the stability of the transcript and/or the rate at which the transcript is produced (49). To determine whether the stability of mature IgG1 transcript was affected by stimulation of CD86 and/or ␤ 2 AR, actinomycin D was added to cultured B cells on day 6 after activation.…”
Section: Stability Of Mature Igg1 Transcript Following Stimulation Ofmentioning
confidence: 99%